The Different Approach of Solution for Multi-objective Fractional Programming Problems Under Fuzzy Environment - Sahoo, Deepanjali; Tripathy, Arun Kumar; Pati, Jitendra Kumar; Parida, Prashanta Kumar (International journal of applied and computational mathematics, 2024)
According to the literature, we can use several linearisation processes to develop a novel technique for solving the multi-objective linear fractional programming problem (MOLFPP) under fuzzy environment. Nevertheless, there hasn’t been any discussion of the comparative studies of solutions in the literature. This article discusses various approaches for applying linearisation techniques to convert multi-objective linear fractional programming problem (MOLFPP) into multi-objective linear programming problem (MOLPP). A comparative analysis is then conducted. In order to showcase our work, we employ several strategies for linearisation, and we explore membership functions such as linear membership function, hyperbolic membership function and exponential membership function.